Antimicrobial susceptibility and resistance of the bacterial population in a seafood processing facility - Beauzec, Michael (University of the Free State, 2024)
Fish and fish products are recommended by international health organisations as a healthy protein option, especially for young children. However, fish is also often associated with foodborne disease outbreaks. The processing of wild caught fish in land-based factories present unique circumstances for bacterial populations to develop and change over time. Bacteria are constantly introduced into the processing environment with the raw material as well as by the staff and factory surroundings. The control of these bacteria can become increasingly difficult due to the development of resistance to disinfectants and the abundance of less effective cleaning agents on the market. Disinfectant resistance and antibiotic resistance have been shown to be linked. The possibility of foodborne pathogens that are also resistant to antibiotics and disinfectants cannot be ruled out. Pathogens that are resistant to cleaning agents may also be resistant to the human immune system which often utilises chemical principles similar to common disinfectants. Resistance genes can also spread across species and even genera. The development of cleaning strategies that can reduce bacterial loads to an acceptable level, whilst also being effective against more resistant bacteria is of crucial importance to the long-term sustainability of the food chain. In the study, a fish processing facility was used to illustrate the ability to isolate the more resistant bacteria in a facility before testing various cleaning agents against these organisms with the concept that most other bacteria would also be susceptible if the most resistant are. The cleaning agents determined to be effective, were used when developing a new cleaning protocol for the site. The cleaning program was implemented at the facility and showed a decreased bacterial load at every point tested. The study shows the application of scientific principles to improve biosecurity measures in an industrial setting, specifically in a seafood processing facility in South Africa.
Keywords: Disinfectants; Food processing; Resistance